New N-(2-phenyl-4-oxo-1, 3-thiazolidin-3-yl)-1, 2-benzothiazole-3-carboxamides and acetamides as antimicrobial agents. Issue 11 (3rd November 2017) - Incerti, Matteo; Vicini, Paola; Geronikaki, Athina; Eleftheriou, Phaedra; Tsagkadouras, Athanasios; Zoumpoulakis, Panagiotis; Fotakis, Charalmpos; Ćirić, Ana; Glamočlija, Jasmina; Soković, Marina
Abstract : 21 novel N -(2-phenyl-4-oxo-1, 3-thiazolidin-3-yl)-1, 2-benzothiazole-3-carboxamides and acetamides have been synthesized and evaluated for their antimicrobial activity. Abstract : A series of 21 novel N -[2-phenyl-4-oxo-1, 3-thiazolidin-3-yl]-1, 2-benzothiazole-3-carboxamides/acetamides (4a–4p ) as well as a series of N ′-(halophenylmethylidene)-1, 2-benzothiazole-3-acetohydrazides (3h–3p ) have been synthesized and evaluated for their antimicrobial activity against eight bacterial and eight fungal species, among them plant, animal and human pathogens and food contaminating species. All compounds appeared to be potent and the best activity was exhibited by compound4d with MIC in the range of 10.7–21.4 μmol mL −1 × 10 −2 and MBC of 21.4–40.2 μmol mL −1 × 10 −2 . The best antifungal activity was observed for compounds4p and3h . Elucidation of the relationship between the antimicrobial activity and molecular properties of the synthesized compounds was also performed. Synthetic intermediates were also tested with several exhibiting good antimicrobial activities. Docking studies for some compounds were performed.